RENEWAL OF THE ATTRACTION POTENTIAL WITH VALUE OF MODULE OF ITS GRADIENT IN ALEXIDZE’S PROBLEM - DUBOVENKO, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Nonlinear boundary Alexidze problem postulates the analytical prolongation of global gravity. Its solution as a simple layer potential is a sequence solutions of external boundary Neumann’s problems for Laplace’s equation for the reason on solution not greatly deviated from given one. Simple layer density is defined from the Fredholm integral equation. The conditions of the corectness are demonstrated.